Some New and Interesting Cyanobacteria from Baghjhoda Pond, Eastern Nepal - Rajopadhyaya, Ritu; Joshi, Sangita; Shrestha, Sabitri; Raj, Shiva Kumar (Himalayan Journal of Science and Technology, 2017)
Cyanobacteria of BaghJhoda pond in three different seasons hav been studied. A total of 8 cyanophycean algae under 6 genera viz., Anabaena, Aphanocapsa, Chroococcus, Oscillatoria, Phormidium and Spirulina were recorded. Anabaena, Oscillatoria and Phormidium were dominant genera and occurred in all three seasons. All the 8 taxa were new for the study area and Anabaena affinis and Anabaena subcylindrical were new records for Nepal.